Analisis Aitem Variable Social Media Fatigue di Kota Bekasi - Firjatullah, Maharani Amelia; Adi, Fahrudin; Azhiim, Rizma Afian; Muzzamil, Ferdy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the reliability and internal validity of Indonesian version of Social Media Fatigue Scale (SMFS). A total of 393 respondents aged 18–25 years participated using a purposive sampling technique. Data were collected using the Social Media Fatigue Scale (SMFS), consisting of 15 items covering cognitive, behavioral, and emotional aspects in 4 levels Likert scale. The statistical analysis results Indonesian version of Social Media Fatigue Scale (SMFS) that used in this research have high reliability with Cronbach’s α 0.947. Furthermore, the internal validity analysis of 15 items shows calculated r-value between 0.652 – 0.751 that consistently higher than critical r-value 0.098. These findings suggest that the adaptation of psychological scale to measure Social Media Fatigue into Indonesian language is suitable for Indonesian culture and behavior.